Self-reported changes in alcohol use behavior among people living with HIV in China after receiving HIV positive diagnosis. (25th January 2018) - Wang, Yan; Chen, Xinguang; Ball, Jacob; Li, Xiaoming; Zhou, Yuejiao; Shen, Zhiyong
Background: Alcohol use remains a significant challenge for treating people living with HIV (people living with HIV). We aimed to examine current use and retrospective self-reported changes in drinking behavior after HIV+ diagnosis in people living with HIV. Method: Survey data were collected from a large random sample of people living with HIV (N = 2964, mean age = 42.5, standard deviation = 12.8) in Guangxi, China. Results: The estimated prevalence rate of current alcohol use was 42.8%. Among current drinkers, 41.7% reported binge drinking and 10.4% reported hazardous drinking. Among the ever drinkers, 45.4% reported reductions in drinking and 19.5% reported quitting after HIV+ diagnosis. Older age, female gender, higher income, being employed, if currently on antiretroviral therapy, and having received an HIV+ diagnosis within a year were positively associated with quitting; and more education, lower income, currently on antiretroviral therapy, and having received an HIV+ diagnosis more than one year were associated with reduced drinking. Conclusion: The time period immediately following receiving an HIV+ diagnosis may represent a window of opportunity for alcohol use intervention in people living with HIV.